Genetic and epigenetic diagnostics of viral susceptibility and inborn errors of immunity - Laura Covill (2024)
In inborn errors of immunity (IEI), as in other monogenic rare diseases, rate of diagnosis has failed to improve beyond 35% despite accessibility of whole genome sequencing for many patients. Here, efforts to improve diagnostics of patients with severe inflammatory diseases in different contexts are presented.We performed three studies on groups of patients who suffered critical COVID- 19 between 2019-2022. In Paper I, we described several patients with an IEI of type I interferon (IFN) which presented unexpectedly late in life after infection with SARS-CoV-2. We diagnosed two patients with biallelic deficiency of IRF7, and characterized the clinical and immunologic phenotypes of seven patients in total. This marks the first time this has been possible in more than an orphan case for this IEI. We further suggested that, based on investigations in two patients, enhanced T cell responses may offer some compensatory immunity for the reduction of type I interferon response. In Paper II, we evaluated a cohort from a single intensive care unit who suffered from critical COVID-19 despite relative health and youth prior to infection. We identified two cases caused by presence of autoantibodies to type I IFN, preventing IFN signalling. We investigated incidence of rare variants in the type I IFN production and signalling pathways compared to controls, as well as screening for rare variants in other IEI genes. We followed up with immunological assays to functionally validate identified variants, and noting a trend towards lower responses in type I IFN signalling in three of six individuals carrying heterozygous very rare, or homozygous rare variants. Paper III investigated genetics of hyperinflammation in COVID-19 patients. Haemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome with some clinical features similar to the cytokine storm experienced by many critical COVID-19 patients, suggesting that variation in cytotoxicity genes associated with HLH may predispose to cytokine storm if triggered by viral infection. Here, we took advantage of large datasets of critical patients and asymptomatic infected provided by the COVID Human Genetic Effort. With thousands of genomes available, we established that variants in genes associated with HLH were not more frequent in critical disease, arguing against a strong pathogenetic overlap.Paper IV described the increased efficacy of a set of diagnostic flow cytometry assays piloted by our lab and reported previously. By evaluating our improved assays in almost 500 donors, including 92 with genetically diagnosed primary HLH, we confirmed that our assays reliably separate data generated from patient samples from control healthy donors or patients with other IEIs not affecting lymphocyte cytotoxicity. Our assays also showed improvement in separating degranulation defects from controls compared to the assays which are the current standard in most laboratories.Finally, Paper V details MAGNET, a novel algorithm for approaching patients who have a predicted rare disease, but for whom whole genome sequencing in a clinical context has been unsuccessful. Using integrated ATAC-seq with patient and parental genomes, and supported by RNA-seq, we analysed two proof-of- concept patients previously diagnosed with HLH and were able to prioritise the variants outside of protein coding regions which cause their disease from genome-wide screening. We optimised this workflow with studies of allelic chromatin accessibility in patients and controls, and identified a strong candidate variant in an IEI patient still unexplained in the clinic.Taken together, these studies have increased our understanding of the genetic aetiology of IEIs, and the speed and rate with which we can diagnose patients suffering these conditions.List of scientific papersI. Respiratory viral infections in otherwise healthy humans with inherited IRF7 deficiency. Campbell TM, Liu Z, Zhang Q, Moncada-Velez M, Covill LE, Zhang P, Darazam IA, Bastard P, Bizien L, Bucciol G, Lind Enoksson S, Jouanguy E, Karabela SN, Khan T, Kendir-Demirkol Y, Arias AA, Mansouri D, Marits P, Marr N, Migeotte I, Moens L, Ozcelik T, Pellier I, Sendel A, Şenoğlu S, Shahrooei M, Smith CIE, Vandernoot I, Willekens K, Yaşar KK, Bergman P, Abel L, Cobat A, Casanova JL, Meyts I, Bryceson YT J Exp Med., 219(7):e20220202 (2022). https://doi.org/10.1084/jem.20220202II. Evaluation of genetic or cellular impairments in Type I IFN immunity in a cohort of young adults with critical COVID-19. Covill LE*, Sendel A*, Campbell TM*, Piiroinen I, Lind Enoksson S, Wahren Borgström E, Hansen S, Ma K, Marits P, Norlin AC, Smith CIE, Kåhlin J, Eriksson LI, Bergman PS, Bryceson YTS J Clin Immunol. 44(2):50 (2024). https://doi.org/10.1007/s10875-023-01641-1III. No association between HLH-associated gene variants and life- threatening COVID-19. Covill LE, Cobat A, COVID Human Genetic Effort, Zhang Q, Bryceson YT. [Manuscript]IV. Efficacy of T cell exocytosis assays for the diagnosis of primary defects in cytotoxic lymphocyte exocytosis. Chiang SCC, Covill LE*, Tesi B*, Campbell TM, Schlums H, Nejati- Zendegani J, Mördrup K, Wood S, Theorell J, Sekine T, Al-Herz W, Akar HH, Belen FB, Chan MY, Devecioglu O, Aksu T, Ifversen M, Malinowska I, Sabel M, Unal E, Unal S, Introne W, Krzewski K, Gilmour KC, Ehl S, Ljunggren HG, Nordenskjold M, Horne AC, Henter JI, Meeths M, Bryceson YT Blood. 144(8):873-887 (2024). https://doi.org/10.1182/blood.2024024499V. ATAC-seq from affected cell types robustly prioritizes pathogenic non-coding variants in patients with monogenic disease. Covill LE, Campbell TM, Holmes TD, Frengen NS, Gustafsson C, Winroth A, Hauenstein J, Vinay Pandey R, Erichsen HC, Redzic D, Yoke CM, Vonlanthen S, Månsson R, Wedell A, Meeths M, Sundin M, Bryceson YT. [Manuscript]